An asymmetric allelic interaction drives allele transmission bias in interspecific rice hybrids - Xie, Yongyao; Tang, Jintao; Xie, Xianrong; Li, Xiaojuan; Huang, Jianle; Fei, Yue; Han, Jingluan; Chen, Shuifu; Tang, Huiwu; Zhao, Xiucai; Tao, Dayun; Xu, Peng; et al. (Nature communications, 2019)
Hybrid sterility (HS) between Oryza sativa (Asian rice) and O . glaberrima (African rice) is mainly controlled by the S1 locus. However, our limited understanding of the HS mechanism hampers utilization of the strong interspecific heterosis. Here, we show that three closely linked genes ( S1A4 , S1TPR , and S1A6 ) in the African S1 allele ( S1-g ) constitute a killer-protector system that eliminates gametes carrying the Asian allele ( S1-s ). In Asian–African rice hybrids ( S1-gS1-s ), the S1TPR-S1A4-S1A6 interaction in sporophytic tissues generates an abortion signal to male and female gametes. However, S1TPR can rescue S1-g gametes, while the S1-s gametes selectively abort for lacking S1TPR. Knockout of any of the S1-g genes eliminates the HS. Evolutionary analysis suggests that S1 may have arisen from newly evolved genes, multi-step recombination, and nucleotide variations. Our findings will help to overcome the interspecific reproductive barrier and use Asian–African hybrids for increasing rice production. Our limited understanding of the hybrid sterility (HS) mechanism in Asian–African rice hybrids hampers utilization of the interspecific heterosis for rice production. Here, the authors identify S1 -mediated HS-related tripartite gamete killer-protector system, and explore their evolutionary relationship.